Olafur Eliasson. - Bergson, Henri; Birnbaum, Daniel; Eliasson, Olafur; Grynsztejn, Madeleine; Speaks, Michael (London New York : Phaidon Press Inc. New York Phaidon Press Limited London, 2002)
Olafur Eliasson is a sculptor, photographer and installation artist whose works explore the relationship between nature and technology, individual experience and collective space. Eliasson draws together in his work art, architecture and science ; the artist explains the simultaneous experience of these disciplines in an open letter, published here for the first time, addressed to a viewer moving through one of his large installations. He will represent Denmark in their Pavilion at the 2003 Venice Biennale.
bibliography p. 159
selected exhibitions and projects, selected interviews and articles p. 146-158
Engels
boek
Keywords: Eliasson, Olafur